Modeling of Steels and Steel Surfaces Using Quantum Mechanical First Principles Methods - Alatalo M; Pitkanen H; Ropo M; Kokko K; Vitos L (Switzerland, 2022)
We describe recent progress in first principles materials modelling applied to iron alloys. First principles methods in general have proven to be an effective way of describing atomic level phenomena in solids. When applied to alloys with chemical disorder, however, the widely used supercell methods turn out to be impractical due to the vast variety of different possible configurations. This problem can be overcome using the coherent potential approximation (CPA), which enables the description of a multicomponent alloy in terms of an effective medium constructed in such a way that it represents, on the average, the scattering properties of the alloy. A bulk alloy, in the case of substitutional random alloys, can thus be described with a single atom while a slab is needed to describe surfaces. The exact muffin-tin orbitals (EMTO) method provides a first principles method that can be combined with the CPA in order to describe steels and other multicomponent alloys. We describe the EMTO-CPA method and provide examples of both bulk and surface properties that can be modelled with this method.
Physical and Numerical Simulation of Materials Processing VII